GENERAL ISSUES CONSIDERING BRAND EQUITY WITHIN THE NATION BRANDING PROCESS - Denisa, COTÎRLEA; Doriana, MORAR (Strategii Manageriale)
The present work-paper was written in order to provide an overview of the intangible values that actively contribute to brand capital formation within the nation branding process; through this article, the author tried to emphasize the differences existent between brand capital and brand equity within the context of the nation branding process, which has became a widely approached subject both in the national and international literature. Also, the evolution of brand capital and brand equity was approached, in order to identify and explain their components and their role, by highlighting the entire process of their evolution under a sequence of steps scheme. The results of this paper are focused on the identification of a structured flowchart through which the process of nation branding -and the brand capital itself- are to be perceived as holistic concepts, integrator and inter-correlated ones, easily understood.The methodology used in order to write the present article resumes to all appropriate methods and techniques used for collecting and processing empirical data and information, respectively to observing, sorting, correlating, categorizing, comparing and analyzing data, so that the addressed theoretical elements could have been founded; in the center of the qualitative thematic research addressed in the present article lie general elements belonging to Romania's image and identity promotion.